2016
DOI: 10.1017/s1049023x15005579
|View full text |Cite
|
Sign up to set email alerts
|

A Course on Terror Medicine: Content and Evaluations

Abstract: An elective course on Terror Medicine, as described, is shown to be feasible and successful. The student participants found the content relevant to their education and the manner of instruction effective. This course may serve as a model for other medical schools contemplating the expansion or inclusion of Terror Medicine-related topics in their curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Within this context, it can be deducted that course designs which were developed and supported by visuals and theoretical information have a positive effect on pre-service teachers' knowledge levels about planning a curriculum-based field trip. These results of the research are compatible with a research in the literature which reveals that enriched elective course content makes contributions to students' knowledge levels (Cole et. al., 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Within this context, it can be deducted that course designs which were developed and supported by visuals and theoretical information have a positive effect on pre-service teachers' knowledge levels about planning a curriculum-based field trip. These results of the research are compatible with a research in the literature which reveals that enriched elective course content makes contributions to students' knowledge levels (Cole et. al., 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Considering these results, it can be stated that in addition to in-class implementations, out-of-class implementations should be carried out so that pre-service teachers' self-efficacy beliefs about planning a curriculum-based field trip are at the highest level, because out-of-class implementations provide an opportunity for pre-service teachers to implement theoretical knowledge only and there self-efficacy was lower than the two other experimental groups. The findings of this research seem to concur with studies which indicated that enriching elective course content and using student-centred teaching methods promote students' interest and awareness of the course (Cole et. al., 2016) and develop their self-confidence positively (Gauthier, Sherman, & Unger, 2015;Hefferan, Heywood & Ritter, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…The course by Cole et al used a variety of teaching modalities, including lectures, videos, and tabletop and hands-on simulation exercises. The subject matter included biological and chemical terrorism, disaster management, mechanisms of injury, and psychiatry [45]. Pfenninger and coworkers developed a course that consisted of 14 modules and that was composed of 2-h units.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 97 included articles, 47 discussed competencies, [16][17][18][19]24,[29][30][31][32][33][34][35][36][37][38][39][41][42][43][44][46][47][48][49][50][51][52][53][54][55]71,84,90,91,95,96,99,100,[103][104][105][106][107][108][109][110] and were split between 2 authors to extract data into an Excel database (Microsoft Corp., Redmond, Washington, USA) that was developed using themes and subthemes from MCI exercise publications to derive statements for the mD. [111][112][113][114]…”
Section: T1: Scoping Reviewmentioning
confidence: 99%